Molecular docking on a synthetic derivative of genistein targeting Estrogen Receptor-α: Investigating the Potential of a Synthetic Genistein Derivative as an Estrogen Receptor Agonist through Molecular Docking Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The objective of this study is to conduct molecular docking analyses on a synthetic genisteinderivative. The compound is hypothesised to mimic oestrogen and function as an endocrine disruptor byactivating the ER-receptor on beta-cells in the pancreas, leading to insulin release. The synthesisedmolecule was subjected to molecular docking using Dockthor, an online research tool for moleculardocking. The Dockthor data was analysed and visualised using the NGL viewer, a web-based softwaredesigned for docking experiments. The results of the analysis were presented through this programme.The analysis of 2D protein-legend interactions was conducted using the BIOVIA Discovery StudioVisualizer. Compound-2 was utilised as the legend, while the oestrogen receptor alpha was identified asthe target receptor for oestrogen. Genistein was synthesised in the present study. This compound isknown to mimic the action of oestrogen by binding to ER-receptors. The effectiveness of drug A'sbinding to the receptor was determined through the analysis of its 2D interactions with the ER- andRamachandran plots using molecular docking.